Development of a Novel Human Single Chain Antibody Against EGFRVIII Antigen by Phage Display Technology - Leila Rahbarnia; Safar Farajnia; Hossein Babaei; Jafar Majidi; Bahman Akbari; Shiva Ahdi khosroshahi (Tabriz University of Medical Sciences, 2016)
Purpose: EGFRvIII as the most common mutant variant of the epidermal growth factor receptor is resulting from deletion of exons 2-7 in the coding sequence and junction of exons 1 and 8 through a novel glycine residue. EGFRvIII is highly expressed in glioblastoma, carcinoma of the breast, ovary, and lung but not in normal cells. The aim of the present study was identification of a novel single chain antibody against EGFRvIII as a promising target for cancer therapy. Methods: In this study, a synthetic peptide corresponding to EGFRvIII protein was used for screening a naive human scFv phage library. A novel five-round selection strategy was used for enrichment of rare specific clones. Results: After five rounds of screening, six positive scFv clones against EGFRvIII were selected using monoclonal phage ELISA, among them, only three clones had expected size in PCR reaction. The specific interaction of two of the scFv clones with EGFRvIII was confirmed by indirect ELISA. One phage clone with higher affinity in scFv ELISA was purified for further analysis. The purity of the produced scFv antibody was confirmed using SDS-PAGE and Western blotting analyses. Conclusion: In the present study, a human anti- EGFRvIII scFv with high affinity was first identified from a scFv phage library. This study can be the groundwork for developing more effective diagnostic and therapeutic agents against EGFRvIII expressing cancers.